THE SIBERIAN DIVISION IN THE TEXTS OF “THE SYBIRAK” QUARTERLY - Kopeć, Zbigniew (Porównania, 2019)
“The Sybirak“ quarterly appeared in the years 1934-1939. One of its goals was to re-evaluate and redefine the place of Siberia in the Polish tradition. The editors tried to partially neutralize the martyrological dimension of Siberia, presenting it as a mere geographic land. The Polish 5th Siberian Rifle Division (Polish: 5 Dywizja Syberyjska, i.e. the 5th Siberian Division) occupied an important place in the Sybirak. Its positive and heroic picture created in the quarterly was seriously disturbed by the book of the Czech diplomat, Jan Šeba, which provoked a number of polemical publications in the quarterly.